Strategic Leadership and Organizational Performance in Small and Medium Enterprises (SMEs) in Asia - Petra Kania Patrecia; Intan Anissa Fitri; Septiyani Septiyani (International Forum of Researchers and Lecturers, 2024)
This study investigates the role of strategic leadership in influencing organizational performance in Small and Medium Enterprises (SMEs) across Asia. The research identifies leadership styles that contribute to enhancing the competitiveness and sustainability of SMEs. A quantitative approach was employed to analyze data from SMEs in countries such as Singapore, Malaysia, and Thailand. The results suggest that transformational leadership, strategic decision-making, and a focus on employee development are key determinants of performance. The paper concludes by discussing the implications for leaders of SMEs in developing countries and offers policy recommendations to foster SME growth.